Zn(OAc)2·2H2O-Catalyzed Efficient Synthesis of 1,8 Dihydrooctahydroxanthenes - Totawar, P. R.; Varala, R.; Pulle, J. S. (Journal of Scientific Research, 2025)
This study used inexpensive and readily available Lewis acid catalyst Zn(OAc)2·2H2O (ZA, 5 mol%) to synthesize 1,8-dihydrooctahydroxanthene derivatives efficiently, with yields of up to 93 %, using a one-pot condensation reaction involving substituted cyclic 1,3-diketones and aldehydes in toluene under reflux conditions.